Potato extract as reducing agent and stabiliser in a facile green one-step synthesis of ZnO nanoparticles. Issue 3 (11th February 2016) - Buazar, F.; Bavi, M.; Kroushawi, F.; Halvani, M.; Khaledi-Nasab, A.; Hossieni, S.A.
Abstract : A facile green recipe was developed to synthesise highly pure, safe and durable zinc oxide nanoparticles (ZnO Nps) using homemade starch-rich potato extract. The ZnO Nps were synthesised using zinc nitrate and potato extract, and the whole reaction is carried out for 30 min at 80 °C. In the synthesis, starch-rich potato extract acted as the reducing agent and as a stabilising layer on freshly formed ZnO Nps. Hexagonal (wurtzite) shaped ZnO Nps with size about 20 ± 1.2 nm were synthesised and characterised using X-ray diffraction, transition electron microscope and scanning microscopy analyses. Fourier transform infrared spectral analysis indicated that highly pure ZnO nanopowders were obtained at higher temperatures. The use of environmentally benign and renewable material as the respective reducing and protecting agents, starch-rich potato extract, as well as a gentle solvent medium (H2 O), offered a simple and quite efficient procedure for the synthesis of ZnO Nps in neutral medium with promising potential for biological and biomedical applications.